The complete chloroplast genome of Eleutherococcus gracilistylus (W.W.Sm.) S.Y.Hu (Araliaceae). (2nd September 2016) - Kim, Kyunghee; Lee, Junki; Lee, Sang-Choon; Kim, Nam-Hoon; Jang, Woojong; Kim, Soonok; Sung, Sangmin; Lee, Jungho; Yang, Tae-Jin
Abstract: Eleutherococcus gracilistylus is a plant species that is close to E. senticosus, a famous medicinal plant called Siberian ginseng. The complete chloroplast genome sequence of the E. gracilistylus was determined by de novo assembly using whole genome next generation sequences. The chloroplast genome of E. gracilistylus was 156 770 bp long and showed distinct four partite structures such as a large single copy region of 86 729 bp, a small single copy region of 18 175 bp, and a pair of inverted repeat regions of 25 933 bp. The overall GC contents of the genome sequence were 36.8%. The chloroplast genome of E. gracilistylus contains 79 protein-coding sequences, 30 tRNA genes, and four rRNA genes. The phylogenetic analysis with the reported chloroplast genomes confirmed close taxonomical relationship of E. gracilistylus with E. senticosus .